Rules of betrayal [large type] - Reich, Christopher, 1961- (Random House Large Print, 2010)
In 1980, a secret American B-52 crashes high in a remote mountain range on the Pakistan, Afghanistan border. Nearly thirty years later, and spanning locales from those peaks to New York City, a terrible truth will be revealed. Jonathan Ransom returns as the resourceful doctor thrown into a shadowy world of double and triple agents where absolutely no one can be trusted. To stay alive, Ransom must unravel the mystery surrounding his wife, an enigmatic and lethal spy who plays by her own rules, and discover where her loyalties truly lie.